2014
DOI: 10.1111/exd.12302
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers in epidermal barrier homeostasis – an approach to mathematical modelling of epidermal calcium dynamics

Abstract: Intact epidermal barrier function is crucial for survival and is associated with the presence of gradients of both calcium ion concentration and electric potential. Although many molecules, including ion channels and pumps, are known to contribute to maintenance of these gradients, the mechanisms involved in epidermal calcium ion dynamics have not been clarified. We have established that a variety of neurotransmitters and their receptors, originally found in the brain, are expressed in keratinocytes and are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Several experimental (Celli et al, 2010; Jungman et al, 2012; Mauro et al, 1998; Menon et al, 1992; Tsutsumi et al, 2009) and computational approaches (Adams et al, 2012, 2015; Cornelissen et al, 2007; Denda et al, 2014) have been used to model or measure Ca 2+ fluxes in epidermis. While initial studies using fixed and sectioned tissue (Mauro et al, 1998; Menon et al, 1992) showed that after acute barrier perturbation, Ca 2+ drops in the viable layers and then recovers as the barrier recovers, a more recent study (Behne et al, 2011) reported a moderate increase in intracellular and extracellular calcium concentration as soon as 30 minutes after barrier perturbation by acetone lipid extraction in hairless mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental (Celli et al, 2010; Jungman et al, 2012; Mauro et al, 1998; Menon et al, 1992; Tsutsumi et al, 2009) and computational approaches (Adams et al, 2012, 2015; Cornelissen et al, 2007; Denda et al, 2014) have been used to model or measure Ca 2+ fluxes in epidermis. While initial studies using fixed and sectioned tissue (Mauro et al, 1998; Menon et al, 1992) showed that after acute barrier perturbation, Ca 2+ drops in the viable layers and then recovers as the barrier recovers, a more recent study (Behne et al, 2011) reported a moderate increase in intracellular and extracellular calcium concentration as soon as 30 minutes after barrier perturbation by acetone lipid extraction in hairless mice.…”
Section: Discussionmentioning
confidence: 99%
“…We recently presented a mathematical model of the epidermal barrier homoeostasis (5). ATP plays a crucial role in cell-cell communication in this model, based on our previous findings that ATP was released after disruption of the epidermal permeability barrier of intact skin or on exposure of cultured keratinocytes to air, and also that application of suramin, a blocker of purinergic receptors, accelerated barrier recovery of the skin and blocked [Ca 2+ ] i elevation (1,2).…”
Section: Discussionmentioning
confidence: 99%
“…Skin is an important organ that provides us with barriers such as protecting from damages and preventing dehydration [20,21], and its internal structure affects barrier functions: for example, diseases such as psoriasis are accompanied by altered structure of the epidermaldermal interface, where the germinative cell population increases and their activity is enhanced [22,23]. Al- though mathematical models have been proposed to understand skin barrier functions [24][25][26][27][28][29][30][31][32], the morphology of the epidermal-dermal interface and its relationship to stem cell patterning has been largely ignored, except for a speculation on the interplay between stem cell activities and the dermal structure [33].…”
Section: Introductionmentioning
confidence: 99%